Impact of oligohydramnios on maternal and perinatal outcome: a comparative study - U., Sreelakshmi; Bindu, Tushara; T., Subhashini (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Oligohydramnios has got significant impact on perinatal outcome and maternal morbidity. Therefore, early detection and its management will help in reduction of perinatal morbidity and mortality, decreased operative interventions. Hence, the present study is undertaken to study the impact of oligohydromnios on perinatal-maternal outcome. Methods: The present study was prospective comparative observational study conducted in the Department of Obstetrics and Gynaecology, Mallareddy Narayana Multispecialty Hospital, reputed teaching hospital from January 2015 to August 2017. The women were divided into study and control groups based on AFI, 100 cases were selected in each group. Results: Out of the 200 women, included in the present study, in study group AFI <5 cm was present in 51% of patients and AFI 5-8 cm in 49% of patients. Doppler abnormalities found in study group (n = 33). 32% of the patients in study group had non-reactive NST while in control group 8%. Caesarean section was performed in 70% of cases in study group as compared to 9% in control group. Foetal distress was the most common indication for LSCS. There were no perinatal deaths in this study. Conclusions: In this study amniotic fluid index of ≤5 cm was commonly associated with increased cesarean section rates, intrauterine growth restriction, Non-reactive NST and abnormal umbilical artery Doppler velocimetry studies. Hence, every case of oligohydramnios needs to be evaluated carefully, early detection and initiation of appropriate treatment and treat the cause if possible.